2015
DOI: 10.1515/ace-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

Predicition Of Compressive Strength In Light-Weight Self-Compacting Concrete By ANFIS Analytical Model

Abstract: Light-weight Self-Compacting Concrete (LWSCC) might be the answer to the increasing construction requirements of slenderer and more heavily reinforced structural elements. However there are limited studies to prove its ability in real construction projects. In conjunction with the traditional methods, artificial intelligent based modeling methods have been applied to simulate the non-linear and complex behavior of concrete in the recent years. Twenty one laboratory experimental investigations on the mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The results indicated that both models showed excellent performance in strength prediction. Vakhshouri and Nejadi used ANFIS to predict compressive strength of self-compacting lightweight concrete [ 29 ]. In their research, an artificial intelligence was applied as a basic approach to simulate the non-linear and complex behaviour of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that both models showed excellent performance in strength prediction. Vakhshouri and Nejadi used ANFIS to predict compressive strength of self-compacting lightweight concrete [ 29 ]. In their research, an artificial intelligence was applied as a basic approach to simulate the non-linear and complex behaviour of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The initiation of the damage processes of concrete structural elements take place in the material structure and several models and theories describing these processes are determined [14][15][16][17][18] similarly as for other materials [19][20][21]. They mey represent the first step in analyzing the behavior of the concrete under different conditions [22,23].…”
Section: Conventional Methods To Limit the Influence Of Forced Deformmentioning
confidence: 99%
“…Among the prediction models, ANN provides more accurate predictions for concrete mechanical properties [19]. In recent years, mechanical properties and the complex behavior of the concrete have been analyzed with the aid and abilities of the artificial intelligence-based methods [20,21]. Prediction of bending strength of the SLC from the mix ingredients and fresh properties is a particularly complex question.…”
Section: Introductionmentioning
confidence: 99%